The Levels of Calcium and Magnesium, and of Selected Trace Elements, in Whole Blood and Scalp Hair of Children with Growth Retardation - Ozmen, Habibe; Akarsu, Saadet; Polat, Fatih; Cukurovali, Alaaddin (Kowsar Corp, 2013)
Objective: Metals such as copper (Cu), zinc (Zn), iron (Fe) are essential for human beings. Chronic metabolic disturbances may result from an excess or deficiency of these metals. Ca and Mg are also nutrient elements and play an important role in biological systems. Thus, it is very important to check regularly trace elements concentration in the body. The purpose of this study was to measure the content of Fe, Cu, Zn, Ca and Mg in whole blood and hair of children with growth retardation compared to that of controls. Methods: A quantitative elemental analysis of whole blood and scalp hair of children with constitutional growth retardation (n=27) and matched controls (n=21) was used to find out correlation and possible changes, between growth retardation and healthy controls. Atomic absorption spectrophotometric (AAS) analysis of quantitative method was used to determine iron, zinc, copper, calcium and magnesium levels of whole blood and scalp hair. Findings: The whole blood levels of Fe and Zn were significantly lower in children with growth retardation (P<0.05), but there were no differences in Cu, Ca and Mg concentrations in whole blood between children with growth retardation and healthy controls. The hair levels of Fe, Zn, Ca and Mg were significantly lower in children with growth retardation when compared to that of controls (P<0.05). The Cu concentrations in the hair of children with growth retardation and healthy controls showed no significant differences (P>0.05). Conclusion: The usefulness and significance of these elements in growth retardation should be discussed more detailed in the light of the most recent data.
Keywords: Whole Blood; Hair; Trace Elements; Growth Retardation; Children